PENGGUNAAN KAYU BAKAR UNTUK RUMAH TANGGA DI DESA SEKITAR TAMAN HUTAN RAYA RAJOLELO BENGKULU - Ban, Putranto; Syariffudin, Joni (Jurnal AGRISEP, 2005)
The study aims to observe the use of fuelwood by people living near Tahura Rajolelo Bengkulu. This study explored two villages as the subjects, desa Dusun Baru I and desa Tanjung Terdana.  Thirty-one (10% IS) households were selected (using stratified random sampling methods) as samples.  Data of fuelwood consumption was measured by directly weighing the fuelwood used for daily activities. Fuelwood preference, methods of collecting fuelwood and other social-economic data were gathered by interviewing the selected families.  From the study it was figured out that; (1) fuelwood consumption of the families in desa Dusun Baru I and Tanjung Terdana were very high, (2) the high consumption   is the impact of the consumption for protecting cattle and the inefficient use of fuelwood for cooking, (3) the fuelwood consumption of the family was significantly affected by the number of people in the family, and (4) women held the main role in collecting fuelwood.